Luigi Mayer, a European painter-traveller at the end of the Eighteenth Century - Spânu, Anda-Lucia (Eikonocity. Storia e Iconografia delle Città e dei Siti Europei, 2020)
Luigi Mayer (1755-1803) was one of the artists which ventured to the Orient in the last decades of the 18th Century. A pre‑Orientalist watercolour painter and drawer, he is known as the author of very accurate views made while holding the official painter position of Sir Robert Ainslie, the British ambassador at Constantinople, for almost two decades (1776-1794).